18F‐Fluorodeoxyglucose uptake and clinicopathological features of recurrent or metastatic endometrial stromal sarcoma. Issue 2 (7th October 2013) - Inoue, Kayo; Tsubamoto, Hiroshi; Kawata, Shuji; Hao, Hiroyuki; Ikeda, Yuki; Oku, Naohiko; Hirota, Seiichi
Abstract Aim Maximum standardized uptake value on 18F‐fluorodeoxyglucose positron emission tomography was evaluated as a predictive surrogate marker in developing treatment strategies for recurrent or metastatic endometrial stromal sarcoma. Methods Clinical information was obtained from records of patients with recurrent or metastatic endometrial stromal sarcoma who underwent surgery or biopsy following 18F‐fluorodeoxyglucose positron emission tomography. Pathological features – including estrogen receptor, progesterone receptor and Ki‐67 expression – were immunohistochemically evaluated. We classified lesions as 'positron emission tomography positive' if the maximum standardized uptake value was 3.0 or higher. Clinicopathological features were compared between patients with positive and negative positron emission tomography findings by using the χ2‐test. Results Among eight recurrent and one metastatic endometrial stromal sarcoma patients, four (44%) had positron emission tomography‐positive findings. Two positron emission tomography‐positive patients were estrogen receptor negative and the five positron emission tomography‐negative patients were estrogen receptor positive (P = 0.073). The Ki‐67 index was 10% or higher in the four positron emission tomography‐positive patients, but less than 5% in the five positron emission tomography‐negative patients (P = 0.003). Three patients with positron emission tomography‐positive tumors received more aggressive treatment (e.g. cytotoxic chemotherapy and additional surgery) than did those with positron emission tomography‐negative tumors. One patient who died of disease had positron emission tomography‐positive tumors, was negative for estrogen and progesterone receptors, and had a 20% Ki‐67 index. Conclusion 18F‐Fluorodeoxyglucose uptake was associated with tumor biology of recurrent or metastatic endometrial stromal sarcoma. 18F‐fluorodeoxyglucose‐positron emission tomography was useful for developing treatment strategies for recurrent or metastatic endometrial stromal sarcoma.